Quantitative Methods in Economics and Finance - Kliestik, Tomas; Valaskova, Katarina; Kovacova, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The purpose of the Special Issue "Quantitative Methods in Economics and Finance" of the journal Risks was to provide a collection of papers that reflect the latest research and problems of pricing complex derivates, simulation pricing, analysis of financial markets, and volatility of exchange rates in the international context. This book can be used as a reference for academicians and researchers who would like to discuss and introduce new developments in the field of quantitative methods in economics and finance and explore applications of quantitative methods in other business areas.